11 articles on Tyre rolling resistance taken fro RAPRA Abstracts database CDROM - various (Technical paper series)
Abstracts (only) of eleven articles compiled together and kept seperately with Reprints (see T-last rack)
Keywords: Rolling resistance; Tyre